Future Of multilateral trading system (Trinity Journal of Management, IT & Media (TJMITM), 2011)
The multilateral trading system of the future is likely to  continue to feel the pressure of protectionist pressures.  However, as brought out trade protectionism would be a  recipe for disaster. Nevertheless, continued support for  more open trade will require other forms of protection, in  the form of better social safety nets for the affected  improved trade and economic infrastructure, supportiv~  domestic policies, etc. on these issues WTO has little  control and these are of domestic policy mix to make  trade opening indisputably acceptable.The multilateral trading system of the future will also  have to take better account of the growing importance of  global value chains. The geographical fragmentation of  the value chain is leading to a structural change in  international trade with more and more goods being  made across a number of countries. The concepts such  as "country of origin" or "resident versus non-resident''  are losing relevance in international economics. The  context calls for measurement of trade flows based on  value added, which will indicate the domestic content of  export, after subtracting direct and indirect imported  inputs. Having the right tools to measure trade flows is  essential in order to have a proper domestic debate  about trade. Global value chains also require taking a  closer look behind border rules and regulations. ·As  ~riffs are gradually reduced either unilaterally or by  virtue of the numerous preferential/ regional trade  agreements being concluded, divergences in domestic  regulatory frameworks require greater attention.
Keywords: multilateral; protectionism; Nevertheless; protection